(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
In recent years, there has been a resurgence of scientific interest in polynitrogen energetic materials. The considerable number of nitrogen bonds contributes to a high formation heat, and their low carbon and hydrogen content results in a good oxygen balance. The main decomposition product is nitrogen and that turns them into environmental-friendly energetic materials attracting research and investment. Very promising chlorine-free oxidizer is Ammonium dinitramide (ADN). In addition to its excellent performance and low ecological impact, this innovative oxidizer provides tactical advantages by eliminating primary metal oxide smoke and secondary aerosol smoke from condensed water vapor and exhaust products. Mitigating the risk of detection, reduction in corrosive combustion products and low flame temperature define Ammonium dinitramide as high energy eco-propellant and pyrotechnic igniter for rocket fuels. The minimized smoke output and reliable combustion characteristics make it well-suited for high-acceleration tactical missiles and underwater propulsion systems. Nevertheless, the high hygroscopicity of Ammonium dinitramide is a property severely influencing the hazards and safety of this promising energetic. To prevent ADN from absorbing moisture during handling, storage and processing the relative humidity of the environment should be below 55% [1]. Beyond its hygroscopic nature, ADN is also known to be incompatible with isocyanates, leading to spontaneous reactions and decomposition. To address the challenges associated with ADN and facilitate its production and application, the research community employs innovative methods. There are ongoing studies investigating the most efficient ADN particle form. The research discovers the utilisation of different polymers to lay uniform ADN particle coating thus improve the absorption of ambient humidity. This paper presents a summary of recent advancements in ADN improvement methods aimed at enhancing stability. Successful solutions for anti-hygroscopicity method are essential for the future application. Tests are being conducted to enhance the conditions of the ADN synthesis for scalable production.